1982
DOI: 10.1111/j.1432-1033.1982.tb06669.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Ellipticine with Model or Natural Membranes

Abstract: Ellipticine is the type of a group of substances used against human cancer. It was shown that ellipticine and 9-methoxyellipticine strongly interact with monolayers of negatively charged phospholipids. In the present paper it is shown by spectrophotometric methods that ellipticine interacts with suspensions of a model membrane with a 131 charge neutralization, and with a natural membrane, both negatively charged. At a physiological pH, ellipticine undergoes protonation in the presence of these membranes. Its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Moreover, the increase of pK a should also be considered as a consequence of increased proton activity at the anionicwater interface, as observed for ellipticine. 43,44) Binding to the membranes, apart from the hemolytic effect, as will be discussed below, can cause an increase in membrane surface area and therefore osmotic fragility. Overall, observations with hydrophobic model systems might suggest that the protonation equilibrium of tested chemicals can be shifted in response to its interactions with different biological macromolecules in vivo as a consequence of the local pH environment.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the increase of pK a should also be considered as a consequence of increased proton activity at the anionicwater interface, as observed for ellipticine. 43,44) Binding to the membranes, apart from the hemolytic effect, as will be discussed below, can cause an increase in membrane surface area and therefore osmotic fragility. Overall, observations with hydrophobic model systems might suggest that the protonation equilibrium of tested chemicals can be shifted in response to its interactions with different biological macromolecules in vivo as a consequence of the local pH environment.…”
Section: Resultsmentioning
confidence: 99%
“…These species can be distinguished by recording the principal UV band of ELL which undergoes dramatic changes upon protonation of the molecule. 43 Both in organic and aqueous buffer solutions the UV band of the neutral form exhibits characteristic vibronic fine structure and its l max value is around 285-286 nm (Fig. 8).…”
Section: CD Absorption Spectroscopic and Computational Docking Invest...mentioning
confidence: 99%
“…A variety of methods, including NMR (Buster et al, 1988;Xiang and Anderson, 1997), EPR spin labels (Cafiso and Hubbell, 1983;Cafiso, 1989;Wallach and Winzler, 1974 ), fluorescence (Wallach and Winzler, 1974;Eidelman and Cabantchik, 1989), and absorbance (Wallach and Winzler, 1974;Kaiser and Hoffmann, 1996), have been used to study the adsorption onto and the transport across bilayer structures. For charged molecules, including some peptides (Kim et al, 1991;McLaughlin, 1991, 1992;Gabev et al, 1989;Chakrabarti et al, 1994), proteins (Zucker et al, 1995;Noy et al, 1992;Kakinoki et al, 1995;Malmstein, 1995;Casals et al, 1993), and drugs (Terce et al, 1982;Aubard et al, 1990;Voelker and Smejtek, 1996), it was found that the electrostatic interaction is the major driving force for the adsorption onto charged liposomes. Studies showed that charged peptides did not adsorb on neutral liposomes composed only of PC lipids, but adsorbed on liposomes composed of a mixture of PC and some charged lipids, such as phosphatidylglycerol (PG), phosphatidylserine (PS), and phosphatidylamine (PA) (Kim et al, 1991;McLaughlin, 1991, 1992;Gabev et al, 1989).…”
Section: Introductionmentioning
confidence: 99%